Pengaruh Terhadap Financial Literacy, Resiko Toleransi, Kemampuan Managemen Resiko Dalam Keputusan Investasi - Joli Afriany; Andy Hakim (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
Investing is a very profitable activity if it is carried out properly and correctly based on the right considerations, but investing can not only have a good impact it can also have a bad impact because of errors in seeing the ability of the company to analyze important things related to impact. the continued operation of a company, decisions in investment are not only profitable but can be detrimental, can be likened to two interrelated coins so it is necessary to know several factors on the company's ability in the financial literature, risk tolerance and risk management ability of a company, each criterion affects the assessment of decisions investment, investment also helps companies in the pace of operations of a company. The investment decision is made by using a decision-making approach, namely the SAW method